Are digital content subscription services still thriving? Analyzing the conflict between innovation adoption and resistance - Jie Yang; Youngkyung Kwon (Journal of Innovation & Knowledge (JIK), 2024)
Currently, the global market for subscription services is facing a crisis of approaching saturation, prompting increased attention to the Asia-Pacific region. Meanwhile, digital content subscription services in Japan are late in the game but are on a continuous upward trend, indicating significant development potential. Despite a global shift towards digital consumption, Japan's strong preference for physical items such as CDs and books, presents an interesting contrast that warrants further research. This study integrates the innovation diffusion and resistance theories to investigate consumers' actual usage and continuous purchase intention of digital content subscription services from both positive and negative perspectives. A questionnaire survey of 250 Japanese digital content subscribers yielded the following conclusions: First, compatibility positively influenced actual usage. Second, trialability negatively impacted actual usage. The unique characteristics of digital content subscription services were identified and compared with those of other innovative services. Furthermore, the tradition barrier exhibited a negative effect on actual usage. Last, actual usage was found to significantly and positively impact continuous purchase intention. By understanding the nuances of the Japanese market, companies can develop effective global strategies to cater to diverse consumer segments and remain competitive in an ever-changing digital landscape.
Keywords: C83; D12; O33; 650; Digital content; Subscription service; Innovation diffusion theory; Innovation resistance theory; Continuous purchase intention